Forecasting Corporate Failure in Malaysian Industrial Sector Firms - Zulkarnain Muhamad Sori; Mohamad Ali Abdul Hamid; Annuar Md. Nassir; Zainal Abidin Mohamad (Asian Academy of Management Journal, 2001)
Financial ratios have long been used as predictor of important events in financial markets of developed economies. Formulating business failure prediction models utilising financial ratios is no exception. However, there is hardly any evidence on failure prediction in developing markets such as Malaysia. This study develops a failure prediction model for industrial sector listed firms that discriminates between 24 failed and non-failed for the period 1980-1996. The findings show that the model correctly and significantly classified 91.1% and 89.3% of the failed and non- failed firms respectively. An alternative prediction model developed based solely on accounting information show similar results. These models predict failure up to 4 years before the actual event. The variables in the final model implies that profits, cash flows, working capital and net worth are important determinants of failures of firms listed in the Kuala Lumpur Stock Exchange.